A Juridical Analysis of Legal Sanctions for Non-Adherent Tuberculosis Patients: Balancing Public Interest and the Right to Health - Erry Prasetyo; Ahmad Ma’mun Fikri (PALAR | PAKUAN LAW REVIEW, 2026)
Tuberculosis remains a major public health challenge in Indonesia due to its long and complex treatment regimen requiring high adherence. Non adherence raises juridical and ethical dilemmas between the obligation of the state to protect public health and the obligation to guarantee the right to health and human dignity. This study analyzes the juridical feasibility of imposing legal sanctions on tuberculosis patients who fail to adhere to treatment. The research uses a normative juridical approach with statute, conceptual, and human rights approaches. The results indicate that Indonesian positive law does not explicitly criminalize non adherence to tuberculosis treatment. Current policy prioritizes administrative and public health approaches such as patient education, treatment supervision, and strengthening healthcare services. Criminal sanctions therefore should not be the primary instrument in addressing treatment non adherence, and should only be considered as ultimum remedium in exceptional circumstances.   Keywords: Tuberculosis, treatment adherence, legal sanctions, public health law, human